Lessons Learned from Initiatives to roll out digital credentials in Europe - Bruno, Maria Luiza (2022)
Day by Day, society is becoming more digital in almost every aspect. Education is also increasingly becoming digitized, considering the acquisition of skills mediated by technology, both in formal and informal learning. In order to recognize the achievement of proficiency in a given competency, it is critical to adopt a digital credential model. Digital credentials are a disruptive model of accreditation, more suited to the digital world we currently find, which can evidence learning through the issuance of a Badge, containing relevant information about the learner, the acquired skill, and the issuing institution.